2019
DOI: 10.1590/1984-70332019v19n3c52
|View full text |Cite
|
Sign up to set email alerts
|

BRS 425: the first runner peanut cultivar related to wild ancestral species

Abstract: BRS 425 is a high-oleic runner peanut cultivar related to wild ancestral parents, partially resistant to early and late leaf spot and spotted wilt. It is large-seeded and contains 46% oil. BRS 425 is adapted to the main peanutproducing regions of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
3
0
6
Order By: Relevance
“…Previous research reported larger seed size (85 g) for LPM 17‐A, larger seed size (48 g) for LPM 21‐A and larger seed size (65 g) for Sun Oleic 97‐R and BRS 425 OL (76 g) (Gorbet & Knauft, 2000; Suassuna et al., 2015; Suassuna, Suassuna, Bogiani, et al., 2019). Because the genotypes related to A. ipaënsis and A. duranensis were selected for adaptation to tropical climate in Brazil, the reduction in seed size is more likely due to the environment when seeds were grown in the United States and therefore, cannot be directly associated with TSW epidemics in the experimental field.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research reported larger seed size (85 g) for LPM 17‐A, larger seed size (48 g) for LPM 21‐A and larger seed size (65 g) for Sun Oleic 97‐R and BRS 425 OL (76 g) (Gorbet & Knauft, 2000; Suassuna et al., 2015; Suassuna, Suassuna, Bogiani, et al., 2019). Because the genotypes related to A. ipaënsis and A. duranensis were selected for adaptation to tropical climate in Brazil, the reduction in seed size is more likely due to the environment when seeds were grown in the United States and therefore, cannot be directly associated with TSW epidemics in the experimental field.…”
Section: Resultsmentioning
confidence: 93%
“…& W.C. Gregory and A. duranensis Krapov. & W.C. Gregory: two prebreeding lines (LPM 17‐A, LPM 21‐A) (Suassuna et al., 2015), four breeding lines (2014‐137 R, 2013‐424, 2013‐268, and 2015‐453), and one cultivar (BRS 425 OL) (Suassuna, Suassuna, Bogiani, et al., 2019). The cultivars TifNV‐High O/L (Holbrook et al., 2017) and Sun Oleic 97R (Gorbet & Knauft, 2000) were used as disease resistant and susceptible checks, respectively (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The trials in Herculândia and Tupã, western São Paulo State, were planted in the beginning of December, and severe spotted wilt epidemics were observed at both locations ( Table 3). The performance of 'BRS 421' and 'BRS 423' exceeded the overall means and checks, as observed for 'BRS 425' (Suassuna et al 2019).…”
mentioning
confidence: 71%
“…Com demanda crescente nos últimos anos, a produção de amendoim tem sido atrativa para produtores de outras regiões do Brasil, em especial no bioma Cerrado. Desde 2010, a Embrapa expandiu o escopo do seu Programa de Melhoramento do Amendoim, incluindo o desenvolvimento de cultivares do tipo Runner alto oleico adaptadas para as principais regiões produtoras de grãos, incluindo o estado do Tocantins, resultando no registro das cultivares BRS 421 OL, BRS 423 OL e BRS 425 OL(SUASSUNA et al, 2019; SUASSUNA et al, 2020). Este trabalho teve o objetivo de avaliar seis linhagens de amendoim do tipo Runner alto oleico(1253( OL, 1952 …”
unclassified